ANALISIS PENGARUH LINGKUNGAN KERJA DAN DISIPLIN TERHADAP KINERJA DENGAN MOTIVASI SEBAGAI VARIABEL MODERATING (Survei pada Tenaga Kependidikan Universitas Slamet Riyadi Surakarta) - Rahayu Triastity, F. Sri Supraptini, Alwi Suddin & (Universitas Slamet Riyadi, 2016)
Survey research conducted at the University of Slamet Riyadi Surakarta(UNISRI), aims to identify and analyze the significance of the influence of theworking environment, discipline, motivation on the performance of educationpersonnel University of Slamet Riyadi Surakarta (UNISRI), with motivationas a moderating variable. The samples using proportional random sampling,the number of samples are 82 educators. Methods of observation and datacollection using questionnaires that have been tested for validity andreliability. Types of qualitative and quantitative data. Mechanical analysisusing classical assumption test, multiple linear regression, t-test, F,coefficient determination and test the absolute difference. The resultsshowed that the working environment and work motivation had no significanteffect on the performance of education personnel UNISRI, work disciplinesignificant effect on the performance of educators UNISRI. Motivationmoderating influence on the performance of the work environment UNISRIeducation personnel. Motivation strengthen the influence of the workingenvironment. Motivation does not moderate influence on the performance oflabor discipline UNISRI education personnel, motivation actually weaken theinfluence of labor discipline on the performance of education personnelUNISRI.Keywords: work environment, discipline, motivation and performance